Potensi Tanaman Obat sebagai Agen Antidiabetes: Review - Wahyudi, Made Suta (IAI Nasional Laa Roiba Bogor, 2026)
Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels. Synthetic drugs such as metformin and sulfonylureas are effective in treating diabetes but have limitations due to side effects. Plants are an alternative medicine because they are natural and safer. This study aims to identify medicinal plants with antidiabetic activity. The research method used was a literature review with searches in PubMed, Google Scholar, and Google using the keywords